2018
DOI: 10.1097/ajp.0000000000000507
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Production of Nociceptive CC Chemokines and sE-Selectin in Patients With Low Back Pain and the Effects of Spinal Manipulation

Abstract: Background:The involvement of inflammatory components in the pathophysiology of low back pain (LBP) is poorly understood. It has been suggested that spinal manipulative therapy (SMT) may exert anti-inflammatory effects.Purpose:The purpose of this study was to determine the involvement of inflammation-associated chemokines (CC series) in the pathogenesis of nonspecific LBP and to evaluate the effect of SMT on that process.Methods:Patients presenting with nonradicular, nonspecific LBP (minimum pain score 3 on 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 47 publications
3
61
1
2
Order By: Relevance
“… 31 33 In addition, in nonspecific patients with LBP, improvements in VAS and ODI scores were closely accompanied by the obvious decline of CCL3 following spinal manipulation. 34 All these works implicate that systematic CCL3 levels may participate the pain production in various disease. In our study, we observed that increased CCL3 levels were related to pain determined by VAS scores and functional disability by ODI index, suggesting serum that CCL3 expression plays a major role in the pain formation of disk degeneration through potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 31 33 In addition, in nonspecific patients with LBP, improvements in VAS and ODI scores were closely accompanied by the obvious decline of CCL3 following spinal manipulation. 34 All these works implicate that systematic CCL3 levels may participate the pain production in various disease. In our study, we observed that increased CCL3 levels were related to pain determined by VAS scores and functional disability by ODI index, suggesting serum that CCL3 expression plays a major role in the pain formation of disk degeneration through potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A kemokinek elősegítik a gyulladást, a gyulladásos sejtek és a neuronok közötti kommunikációban, a fájdalom transzmissziójában játszanak szerepet. A fájdalom és a különböző kemokinek kapcsolatát eddig még kevés vizsgálat elemezte [36].…”
Section: Kemokinek Egyéb Vizsgált Lehetséges Biomarkerekunclassified
“…Akut és krónikus derékfájdalomban szenvedők szérummintáiban összehasonlítva a CCL2, CCL3, CCL4 kemokinek szintjeit egy kontrollcsoport mintáival, szignifikánsan emelkedett kemokinszinteket írtak le a fájdalomban szenvedők csoportjában (63 fő). Ezenfelül a CCL4 szintje jelentősen magasabb volt az akut derékfájdalomban szenvedők körében, mint a krónikus derékfájdalom miatt vizsgált egyénekben [36].…”
Section: Kemokinek Egyéb Vizsgált Lehetséges Biomarkerekunclassified
“…Few studies have suggested possible pathophysiological mechanisms in LBP as the increase of the inflammatory biomarkers tumor necrosis factor-α (TNF-α), interleukins (IL)-1α, IL-1β, IL-6, IL-17, chemokines (CCL) 2 and 4, and a decrease of IL-10, anti-inflammatory cytokines. 4 , 5 , 6 , 7 , 8 , 9 These biomarkers (e.g., cytokines) are small secreted proteins released by immune cells populations, predominantly by T Helper and macrophages cells. They have a specific effect on the interactions and communication between cells.…”
Section: Introductionmentioning
confidence: 99%